How Can Early Christian Thought Inform Doughnut Economics? - Stuart, David (Studies in Christian ethics, 2024)
Doughnut Economics is an economic model designed to overcome the negative impact that the crude use of Gross Domestic Product (GDP) can have on both society and the environment. As the model becomes more widely adopted it is important to explore the model from a theological perspective. Early Christian economic thought provides a way of exploring and challenging many of the fundamental ideas and conceptualisations of the DE model. DE has much to learn from early Christian thinkers. Firstly, a non-absolutist understanding of property can fuel calls for a more radical distribution of wealth than called for in DE, with an even greater emphasis on the process and benefits of individual almsgiving. Secondly, it shows how the limitations of the social foundation of DE has much to learn from the positive value of the ascetic lifestyle promoted by some early Christian thinkers. Finally, at a time when there are understandable concerns about the limits of the ecological ceiling, early Christian thought offers both hope and a call to action.